Potential Growth in Emerging Asia - Anand, Rahul (IMF Working Papers; Working Paper, 2014)
Using three distinct approaches-statistical filtering, production function, and multivariate model- this paper estimates potential growth for China, India, and five ASEAN countries (Indonesia, Malaysia, the Philippines, Thailand, and Vietnam) during 1993-2013. The main findings include: (i) both China and India have recently exhibited a slowdown in potential growth, largely reflecting a decline of total factor productivity (TFP) growth; (ii) by contrast, trend growth for the five ASEAN countries has been rather stable and might even have increased marginally, with the notable exception of Vietnam;(iii) over the longer term, demographic factors will be much more supportive in India and some ASEAN economies than in China, where working-age population should start shrinking, with the overall dependency ratio climbing by the end of this decade. Improving or sustaining potential growth calls for broad structural reforms.